Condensation nuclei counts
This is a graph of looking at condensation nuclei counts. This is looking at the vertical scale as a log of the number. The log of the number meaning a two would be on the order of what we’re talking about as a hundred. So during the summertime, we have the high levels. The summertime, remember, is January, February, March, October, November, December. We usually would go down in late October and spend November, December, January, and February down there and then return in late February, early March. But during the summertime, the condensation nuclei counts are approximately a hundred per cubic meter. When we go to the wintertime, they drop down well below ten and sometimes down in less than two or three particles per cubic centimeter. So they get extremely low levels during the Antarctic wintertime, higher levels during the summertime; and this is all due to transport, mainly of sea salt, from the oceans surrounding Antarctica and some from continents around Antarctica.